MEDITATION: A DISCRIMINATING REALIZATION - John B Chethimattam (Journal of Dharma, 1977)
Meditation has arrived at the right time. At the height of scientific and technological progress and material affluence, man still feels the need to take stock of himself and to ask which way lies real progress. Maharishi Mahesh Yogi's TM and various yoga techniques and psychological relaxation methods have pointed out that man has an infinite vista of exploration within himself. Most methods of meditation have been goal-oriented, focusing attention on the one, infinite reality that is the ultimate end of man. Ancient Yoga proposed to arrest the dissipating outward move- ment of the mind and its faculties rooted in Prakriti, to bring it to a certain balance of functions and to subordinate it to the sub- jectivity of Purusha that stands isolated from this process as a pure witness. Theistic Hinduism of Ramanuja, Madhava and others, proposed a method for collecting all one's psychological powers through concentration and subordinating them through devotion to the one Lord, who is the immutable, infinite conscious- ness. Psychologists and psychiatrists describe meditation ra- ther, "like coming home", a technique "to find, to re- cover, to come back to something of ourselves we once dimly and unknowingly had and have lost without knowing what it was", "an access to more of our human potential or being clo- ser to ourselves and to reality"]. Zen and TM have struck a compromise between these two extremes and fixed their attention on a formless, nameless area of objective silence. But Siddhartha Gautama Buddha's method of "right mindfulness" and Samadbi, and Sankara's "Advaita Vedanta" present a more meaningful religious synthesis of the two positions. Buddhism presents a practical approach while Advaita emphasizes a more philosophical method.